2015
DOI: 10.1155/2015/386409
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric Characteristics and Management of Patients with Postpartum Psychosis in a Tertiary Hospital Setting

Abstract: Background. Postpartum psychosis is the most severe and uncommon form of postnatal affective illness. It constitutes a medical emergency. Acute management emphasizes hospitalization to ensure safety, antipsychotic medication adherence, and treatment of the underlying disorder. Objective. The aim of the study was to determine the obstetric characteristics and management of patients with postpartum psychosis in a tertiary centre in North-Western Nigeria. Methodology. This was a 10-year retrospective study. Recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 19 publications
2
10
0
Order By: Relevance
“…8,9,10 Duration of Illness Most of the cases (93.33%) presented within 15 days after delivery. This finding is supported by some studies, 11 but not by others 12 where in most of cases, illness occurred after two weeks.…”
Section: Paritysupporting
confidence: 59%
See 1 more Smart Citation
“…8,9,10 Duration of Illness Most of the cases (93.33%) presented within 15 days after delivery. This finding is supported by some studies, 11 but not by others 12 where in most of cases, illness occurred after two weeks.…”
Section: Paritysupporting
confidence: 59%
“…Shehu et al (2015) have found physical comorbidities in around 77% of patients. 11 Some drugs like chloroquine and ciprofloxacin were also responsible for idiosyncratic manifestation of psychosis. 6.67% developed psychosis following chloroquine and ciprofloxacin administration respectively.…”
Section: Precipitating Factorsmentioning
confidence: 99%
“…In total these five studies reported on 167 women with a PSMD. Three studies (Ndosi and Mtawali 2002;Adefuye et al 2008;Shehu and Yunusa 2015) calculated prevalence using the number of births in the hospital during the period of ascertainment as the denominator (162 women with a PSMD in a total of 69,055 births). The other two studies (Bang et al 2004;Oyewole et al 2014) used women who did not develop psychosis in the study populations as the denominator (5 women with a PSMD in a total of 952 women).…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…The other two studies (Bang et al 2004;Oyewole et al 2014) used women who did not develop psychosis in the study populations as the denominator (5 women with a PSMD in a total of 952 women). Two studies (Adefuye et al 2008;Shehu and Yunusa 2015) extracted clinical information from audits of inpatient medical records to identify women diagnosed with postpartum psychosis retrospectively. Two studies (Ndosi and Mtawali 2002;Oyewole et al 2014) were prospective and conducted within maternity settings.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…In one of study most of the patients with post partum psychosis had no formal education. 10 Although the post partum psychosis is over represented in illiterate group, it will not be fair to hypothesize that post partum psychosis is more common in illiterate since majority of rural females are otherwise illiterate.…”
Section: Socio-economic Statusmentioning
confidence: 99%